JETT 2022
DOI: 10.47750/jett.2022.13.02.005
|View full text |Cite
|
Sign up to set email alerts
|

ESL teachers and students' perceptions toward blended learning during Covid -19 pandemic

Abstract: The global disruption caused by the COVID-19 epidemic has unquestionably created untold, indescribable, and pervasive issues in the Philippines' educational system. Teachers have been challenged with implementing distance learning modes from the beginning of the pandemic, often without adequate guidance, training, or resources. The researcher was inspired by the influence of COVID 19 on professors and students at Bulacan State University to investigate the feasibility of establishing a transformative learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…In Leon's (2022) study titled "ESL Teachers and Students' Perceptions toward Blended-Learning during COVID-19 Pandemic," it was found that the participants shared a common view that blended learning did not have a favorable effect on students' learning in the "Purposive Communication" course (Leon, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…In Leon's (2022) study titled "ESL Teachers and Students' Perceptions toward Blended-Learning during COVID-19 Pandemic," it was found that the participants shared a common view that blended learning did not have a favorable effect on students' learning in the "Purposive Communication" course (Leon, 2022).…”
Section: Related Workmentioning
confidence: 99%